Synthesis and performance assessment of semiconductor photocatalysts - Lau, Wei Siew. (2011)
A combination technique of sol-gel and hydrothermal treatment was used to synthesize nitrogen doped TiO2-based photocatalysts at different hydrothermal temperature and time. Photocatalytic activities of synthesized photocatalysts were determined by photocatalytic degradation of methylene blue in comparison with commercial P25.